Upaya Mitigasi Bencana Abrasi Pada Kawasan Pesisir Desa Aeng Batu-Batu, Kecamatan Galesong Utara, Kabupaten Takalar - Musfiratul Muthmainnah; Rudi Latief; Rimba Arief (Fakultas Teknik Universitas Bosowa, 2022)
The purpose of this study was to determine what factors influence the occurrence of abrasion in Aeng Batu-Batu Village and to identify mitigation efforts for abrasion disaster in Aeng Batu-Batu Village, North Galesong District, Takalar Regency.The variables used in this study consisted of 8 (eight) independents, namely: (1) Vegetation Condition, (2) Topography and Slope Slope, (3) Soil Type, (4) Beach Form, (5) Wind, (6) Ocean Wave , (7) Tidal, and (8) Sand Dredging Activities. The analytical method used is the Multiple Linear Regression Analysis Method and the Descriptive Analysis Method. Based on the results of the analysis, there are several factors that influence the occurrence of abrasion in Aeng Batu-Batu Village, namely natural factors in the form of vegetation conditions, topography and slopes, sea waves and tides. The artificial factor is sand dredging activity. The form of mitigation efforts that can be taken to minimize the occurrence of abrasion disasters is to carry out a soft structure development program and physical structure, as well as the preparation of a regional regulation on the prohibition of sand dredging activities and counseling, socialization and simulation of abrasion disaster mitigation.